Spectroscopy and thermal studies of valsartan compounds with metals Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) in the solid state - Siqueira, A. P.C.; Ionashiro, E. Y.; Bannach, G. [UNESP]; De Souza, A. R. [UNESP]; Morgon, N. H.; Soares, M. A.; Siqueira, A. B.; Leles, M. I.G. (Elsevier, 2021)
Solid-state M-Val compounds were synthesized, where M stands for bivalent metals (Mn, Fe, Co, Ni, Cu, and Zn), and Val stands for valsartanate ion (C24H27N5O32−). The thermal and spectroscopic study of the compounds was performed using TG-DSC, FTIR, DRX, as well as the evolved gas analysis (EGA) by TG/DSC-FTIR. The thermoanalytical results showed information about the stoichiometry of the compounds (1:1), the degree of hydration, and thermal behavior. The EGA results allowed the identification of the aliphatic hydrocarbons, carbon monoxide, carbon dioxide, and ammonia for both Valsartan and metal compounds. The theoretical and experimental spectroscopic data suggested the possible modes of coordination of the ligand with the metal ions by coordinating bonding with the oxygen of the carboxylate and the tetrazole group's nitrogen. The association of Cu (II) and Co (II) metal ions with Val improves the antimicrobial activity against E. coli.
Keywords: Drug; Metal ion; Thermal behavior; Valsartan